2012
DOI: 10.1007/s11010-012-1516-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholesterol on lipogenesis and VLDL–TG assembly and secretion in goose primary hepatocytes

Abstract: To investigate how cholesterol induces hepatocytic steatosis, we investigated the effect of cholesterol on hepatic lipogenesis and the assembly and secretion of very-low-density lipoprotein-triglycerides (VLDL-TGs) in goose primary hepatocytes. We found that cholesterol at 20 μg/ml increased the concentrations of extracellular VLDL, intracellular cholesterol, and intracellular TGs, while cholesterol at 30 μg/ml had a reduced effect (p < 0.05). Additionally, cholesterol at 20 μg/ml, but not at 10 or 30 μg/ml, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Most apolipoproteins, endogeneous lipids, and lipoproteins are synthesized in the liver, which depend on the cellular integrity and functions (Han et al, 2013). In the present study, treatment of male rats with FLU (10 mg or 500 mg/kg) exhibited significant increases in both serum and liver TL, TC and TG in addition to serum LDL-C levels, in a dose dependent manner, when compared to the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Most apolipoproteins, endogeneous lipids, and lipoproteins are synthesized in the liver, which depend on the cellular integrity and functions (Han et al, 2013). In the present study, treatment of male rats with FLU (10 mg or 500 mg/kg) exhibited significant increases in both serum and liver TL, TC and TG in addition to serum LDL-C levels, in a dose dependent manner, when compared to the control group.…”
Section: Discussionsupporting
confidence: 50%
“…Excessive production of TG-rich VLDL (VLDL-TG) contributes to hypertriglyceridemia [30]. Many genes are involved in the assembly and secretion of VLDL-TG, such as the microsomal triglyceride transfer protein (MTP) and apolipoprotein A-V (apoA-V) [31,32]. Previous studies showed that testosterone regulates hepatic MTP expression in rats and mice [25,33].…”
Section: Discussionmentioning
confidence: 99%
“…There have studies demonstrated that the mRNA expressions of fatty acid synthase (FAS), acetyl‐CoA carboxylase‐ α (ACC α ), sterol regulatory element binding protein‐1c (SREBP‐1c) and extracellular VLDL concentration in goose primary hepatocytes were increased after incubated with cholesterol (Han et al., ). Mannisto et al.…”
Section: Discussionmentioning
confidence: 99%